Family caregiver communication in oncology: advancing a typology. Issue 4 (4th June 2015) - Goldsmith, Joy; Wittenberg, Elaine; Platt, Christine Small; Iannarino, Nicholas T.; Reno, Jenna
Abstract: Objectives: The quality of communication between the patient and family caregiver impacts quality of life and well‐being for the two; however, providers have few tools to understand communication patterns and assess the communication needs and preferences of caregivers. The aims of this study were to examine family communication patterns among oncology patients and their caregivers and to identify common characteristics among four different types of family caregivers. Methods: Nurses recruited oncology patient–caregiver dyads through a large cancer treatment center in the Southeast. Patients and caregivers were separated from one another and interviewed during chemotherapeutic infusions. Interviews were recorded, transcribed, coded, and thematized. Results: A sample of 24 patients and their caregivers (n = 48) were interviewed. The majority of dyads (21, 88%) shared the same family communication pattern. Common caregiver communication features support previous work identifying four caregiver communication types: Manager, Carrier, Partner, and Lone caregivers. Manager caregivers lead patients by utilizing extensive medical knowledge, whereas Carrier caregivers were led by patients and described tireless acts to maintain the family and avoid difficult conversations. Partner caregivers facilitated family involvement and open communication on a variety of topics, while Lone caregivers focused solely on biomedical matters and a hope for cure. Conclusions: Caregiver communication types were corroborated by patient–caregiver descriptions of caregiving. However, more information is needed to ascertain the variables associated with each caregiver type. Future work to improve identification of caregiver types and create targeted caregiver care plans will require further study of health literacy levels and tested communication interventions per type. Copyright © 2015 John Wiley & Sons, Ltd.